Review of Inflammatory Bowel Disease in China - Lingna Ye; Qian Cao; Jianfeng Cheng (The Scientific World Journal)
Inflammatory bowel disease mainly consisting of ulcerative colitis and Crohn’s disease has been rising gradually during the last two decades in China. In this review article, we provide the latest epidemiological trends in incidence, prevalence, and mortality of IBD patients in China and summarize the risk factors and genetic susceptibility of Chinese IBD patients. We also compare these characteristics to those of IBD patients in Western countries.